Modelos para avaliação de projetos de redes de teleprocessamento - Castro, Cláudio Vieira de (1973)
Design of simulation models for Data Transmission Systems operating interactively. It is supposed that a set of terminals is connected, through concentrators, to one central computer or a computer network. For each system, a model codified in GPSS (General Purpose Simulation System - IBM) was developped and the results of the simulation of these Systems, operating under different circunstances, makes evident the usefulness of such models in Teleprocessing Network design evaluation.